ANALISIS PEMAHAMAN RELIGIUSITAS PEGAWAI KEMENTERIAN AGAMA TERHADAP MINAT PEMBAYARAN ZAKAT PROFESI DI KABUPATEN KOLAKA UTARA. - Regina Putri (Jurnal Syariah Hukum Islam, 2019)
The Ministry of Religion in North Kolaka Regency is an institution formed by the government with the aim of carrying out affairs in the religious sector within the government. Zakat is one of the acts of worship that is required by Allah SWT to every Muslim. The commands in the Al-Qur'an are always juxtaposed with the orders for prayer. The importance of paying zakat because this command contains a social mission which has the intended purpose, among others, to solve the problem of poverty. This shows how important it is to pay zakat as one of the pillars of Islam. The formulation of the problem in this study are: How is the interest in paying professional zakat on Ministry of Religion employees in North Kolaka Regency and How is the understanding of employee religiosity towards the interest in paying professional zakat in North Kolaka Regency. The objectives of this study are: To determine the interest in paying professional zakat on employees of the Ministry of Religion in North Kolaka Regency. And to find out how the understanding of the Religious Affairs of the Ministry of Religion employees towards the interest in paying professional Zakat in North Kolaka Regency. The research method used is qualitative research with a descriptive type that is subject to the Ministry of Religion's employees on the Interest of Professional Zakat Payment in North Kolaka Regency. Data collection techniques include interviews and documentation. The research instrument used was an interview guide for the Ministry of Religion's employees in North Kolaka Regency, along with documentation in the form of interview sheets, data on the amount of zakat disbursements and documentation. The data analysis techniques used were data reduction, data triangulation, data presentation, drawing conclusions and verification The results showed that the Religious Understanding of Zakat at the Ministry of Religion in North Kolaka Regency generally has a fairly good understanding of zakat, both in terms of the rules for paying zakat and people who are entitled to receive zakat and they are also able to explain some hadiths or arguments about zakat. With zakat interest from the ministry of religion, the ministry of religion is indeed very good, because they understand that zakat is important and must be done. Especially those who have jobs that earn more.